The link between central carbon metabolism and replication in bacillus subtilis - Pitoulias, Matthaios G. (2020)
It is a common observation that the growth rates of cells, specifically carbon metabolism is inextricably linked with replication. While progress has been made into both fields of metabolism and replication individually, the underlying mechanism demonstrating how these two pathways intercept is yet to be discovered. Recent genetic data from our collaborators indicate a coupling between replication and the lower part of glycolysis. Specifically, the spotlight is under the metabolic PykA / CcpN / YqfL cascade and the replication regime, referring to the helicase DnaC, the helicase loader DnaI, the primase DnaG and the polymerase DnaE. We tried to investigate the above hypothesis using biochemical and biophysical in vitro approaches such as Electrophoretic Mobility Shift Assays (EMSAs), Helicase Unwinding and Primer Extension assays, Mass Spectrometry and Surface Plasmon Resonance (SPR). Most importantly, our data revealed a functional interplay between the Pyruvate kinase PykA and the lagging strand polymerase DnaE through a series of primer extension assays. Additionaly, we discovered novel functional effects in vitro mediated by other metabolic proteins including PykA on the activities of the helicase DnaC, and also a reversal of the DnaG-mediated stimulation of the DnaC helicase activity.